2018
DOI: 10.1194/jlr.r083451
|View full text |Cite
|
Sign up to set email alerts
|

Lipid transfer proteins in the assembly of apoB-containing lipoproteins

Abstract: Running Title: Lipid transfer proteins and lipoprotein assemblyAbbreviations used: ARF1, ADP ribosylation factor 1; AUP1, ancient ubiquitous protein 1; Blps, apoB-containing lipoproteins; CIDEB, cell death-inducing DFF45-like effector B; COPII, coat protein complex II; cLDs, cytoplasmic lipid droplets; ER, endoplasmic reticulum; MTTP, microsomal triglyceride transfer protein; PLTP, phospholipid transfer protein AbstractA better understanding of intracellular lipoprotein assembly may help identify proteins with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 87 publications
3
97
0
Order By: Relevance
“…These independent associations of LCAT and PLTP activity with an elevated FLI finding agree with the hypothesis that hepatic fat accumulation may enhance further increments in circulating LCAT and PLTP activities resulting from dysglycaemia and central obesity. On the other hand, animal experiments would suggest a pathogenic role for intracellular LCAT and PLTP as such in modulating NAFLD development . Mice studies have revealed that LCAT may aggravate hepatocellular endoplasmatic reticulum stress, although genetic LCAT deficiency could enhance triglyceride accumulation in the liver .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These independent associations of LCAT and PLTP activity with an elevated FLI finding agree with the hypothesis that hepatic fat accumulation may enhance further increments in circulating LCAT and PLTP activities resulting from dysglycaemia and central obesity. On the other hand, animal experiments would suggest a pathogenic role for intracellular LCAT and PLTP as such in modulating NAFLD development . Mice studies have revealed that LCAT may aggravate hepatocellular endoplasmatic reticulum stress, although genetic LCAT deficiency could enhance triglyceride accumulation in the liver .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, animal experiments would suggest a pathogenic role for intracellular LCAT and PLTP as such in modulating NAFLD development . Mice studies have revealed that LCAT may aggravate hepatocellular endoplasmatic reticulum stress, although genetic LCAT deficiency could enhance triglyceride accumulation in the liver . PLTP deficiency results in attenuated hepatic triglyceride accumulation in mice and may impair apoB secretion from hepatocytes by increasing intracellular oxidant status …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting retinyl esters are incorporated with other neutral lipid esters (i.e., triacylglycerols and cholesteryl esters) and intact carotenoids into chylomicrons . Chylomicron assembly also requires the synthesis of microsomal triglyceride transfer protein (MTTP) and apolipoprotein B (apoB) . In the circulation much of the chylomicron triacylglycerol is hydrolyzed by lipoprotein lipase in extrahepatic tissues resulting in the production of a “chylomicron remnant.” The liver rapidly takes up the chylomicron remnants, and there is evidence that the retinyl esters are rapidly hydrolyzed and reesterified by LRAT during this process …”
Section: Intestinal Absorption Of Vitamin a And Carotenoidsmentioning
confidence: 99%
“…The triglycerides are either packaged into chylomicrons, a lipid rich lipoprotein containing the unique non-exchangeable apolipoprotein Apo B48, or are stored as lipid droplets that may later be mobilized for the assembly of chylomicrons. The non-covalent coupling of triglycerides with apo B48 occurs co-translationally to initiate the assembly of chylomicrons and is mediated by the lipid transfer protein, microsomal triglyceride transfer protein (MTTP), whose function has been reviewed by Hussain and Sirwi (1). A deficiency of MTTP results in abetalipoproteinemia, a disease associated with low plasma lipids and vitamin A deficiency.…”
Section: Transfer Of Lipid From Diet To Tissuementioning
confidence: 99%